2017
DOI: 10.5194/angeo-35-11-2017
|View full text |Cite
|
Sign up to set email alerts
|

On the response of quasi-adiabatic particles to magnetotail reconfigurations

Abstract: Abstract. We investigate the response of quasi-adiabatic particles to dynamical reconfigurations of the magnetotail field lines. Although they travel through a sharp field reversal with a characteristic length scale smaller than their Larmor radii, these quasi-adiabatic particles experience a negligible net change in magnetic moment. We examine the robustness of such a quasi-adiabatic behavior in the presence of a large surging electric field induced by magnetic field line reconfiguration as observed during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The proton motion in Mercury's magnetotail is adiabatic in the region outside the central plasma sheet as demonstrated in previous test‐particle simulations (Delcourt et al, 2017) during magnetic quiet period. In other words, the first adiabatic invariant ( μ=12mv2false/B) conserves.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The proton motion in Mercury's magnetotail is adiabatic in the region outside the central plasma sheet as demonstrated in previous test‐particle simulations (Delcourt et al, 2017) during magnetic quiet period. In other words, the first adiabatic invariant ( μ=12mv2false/B) conserves.…”
Section: Introductionsupporting
confidence: 63%
“…However, the radial variation of κ value indicates this energization process may not be adiabatic. The dawn‐dusk asymmetry of κ value also demonstrate the strong non‐adiabatic cross‐tail acceleration in Mercury's magnetotail (Delcourt et al, 2017; Ip, 1987; Sun et al, 2018). A previous study on the Earth's magnetotail also finds the dawn‐dusk asymmetry in κ for both ions and electrons (Espinoza et al, 2018).…”
Section: Discussion and Summarymentioning
confidence: 92%
“…Mercury's relatively small magnetosphere results in the temporal and spatial scale of the electric and magnetic field variations to be comparable to those of plasma motion at the planet. Under such circumstances, plasma motion and field variation strongly affect each other, resulting in a possible non-adiabatic energization of plasmas which leads to significant plasma heating (e.g., Delcourt et al, 2002Delcourt et al, , 2007Delcourt et al, , 2017Zelenyi et al, 2007). In the following subchapters, we focus on the different possible mechanisms of particle energization expected in Mercury's magnetosphere.…”
Section: Particle Energization In Mercury's Magnetospherementioning
confidence: 99%
“…Second, characteristics of electron PADs may implicate the electron acceleration/cooling mechanisms. For example, the pancake‐type PAD is believed to be a consequence of betatron acceleration, which is driven by the enhancement of magnetic field strength on both large and small scales (e.g., Fu et al, 2011; Fu, Khotyaintsev, et al, 2013; Fu, Xu, et al, 2019; Liu, Fu, Xu, Wang, et al, 2017; Liu, Fu, Cao, Xu, et al, 2017; Liu, Fu, Xu, Cao, et al, 2017); the cigar‐type PAD is suggested as a result of Fermi acceleration due to the shrinking of magnetic field lines (e.g., Fu et al, 2011; Lu et al, 2016; Liu, Fu, Xu, Wang, et al, 2017) or betatron cooling driven by the weakening of the local magnetic field (e.g., Fu, Khotyaintsev, et al, 2013; Liu, Liu, Xu, & Zhao, 2018); the isotropy type of PAD is thought as a result of the wave‐particle interactions (e.g., Fu, Khotyaintsev, Vaivads, André, Sergeev, et al, 2012) or the nonadiabatic electron motion along the strongly curved magnetic field lines (e.g., Delcourt et al, 2017); the butterfly type of PAD is suggested to be a combinational consequence of betatron cooling and magnetic mirror effect (e.g., Liu, Fu, Cao, Xu, et al, 2017); and the rolling‐pin distribution is thought as a result of the global‐scale Fermi acceleration together with local‐scale betatron acceleration (Liu, Fu, Xu, Cao, & Liu, 2017). Therefore, investigating the characteristics of PAD of suprathermal electrons can improve our understanding of electron dynamics in the Earth's magnetotail.…”
Section: Introductionmentioning
confidence: 99%